School Internal Organisation as a Correlate of Teachers’ Attrition and Retention in Bauchi Metropolis Secondary Schools, Nigerian - Adamu, Martha Maigari; Adam, Dr. Muhammad (Advances in Social Sciences Research Journal, 2021)
This paper studied school internal organisation as a correlate of teachers’ attrition and retention in Bauchi metropolis secondary schools. To determine the extent to which compensation and benefits as relates to teachers’ attrition and retention is among the objectives of the study. Correlational research design was adopted. The population of the study consisted of all teachers’ of public secondary schools in Bauchi State. A sample of 50 was selected using table for determining sample size by research Advisor. The simple random sampling technique was employed in selecting the sample. A questionnaire was adapted from modified MetLife Survey of the American Teacher instrument from 2006 and UNESCO (2014), titled “Determinants of Teachers Attrition and Retention (DETAREQ)”. The validity of the instrument was ascertained. A reliability of .71 obtained using Cronbach Alpha. A multiple regression was used to analyzed data obtained. The results showed that Compensation and benefit has positive relationship with Teachers attrition and retention to a large extent. Therefore, Refresher courses /Training, Seminars /workshops should be organized by the Ministry of Education to sensitize and educate teachers to change their mentality and provide them other benefits to attract and keep them in the profession, were recommendations made among others.